Impact on bus superstructure due to rollover - Ali, Md. Liakat (2008)
Bus is a popular and common transport in the world. The safety of bus journey is a fundamental concern. The risk of injuries and fatalities is severe when the bus structure fails during a rollover accident. Adequate design and sufficient strength of the bus superstructure can reduce the number of injuries and fatalities. This study examines the deformation response of a typical bus structure during a rollover test simulation. A simplified box structure was modeled using finite element analysis software and simulated in a rollover condition according to the requirements of UNECE Regulation 66. The same box model was fabricated to validate the results obtained from finite element analysis simulation. After successful validation of the box model simulation, a complete bus structure with forty four passengers’ capability was developed using finite element analysis software. The simulation of the bus was conducted using the same inputs used in box model simulation. Four simulations have been conducted to get the dimensions of different members of the superstructure of bus which is capable to protect rollover crash. The analysis suggested that, the failure of bus frame during rollover situation is basically dependent on the total mass of bus and on the strength of bus superstructure.